2022
DOI: 10.3390/ma15072457
|View full text |Cite
|
Sign up to set email alerts
|

Hole Morphology and Keyhole Evolution during Single Pulse Laser Drilling on Polyether-Ether-Ketone (PEEK)

Abstract: Polyether-ether-ketone (PEEK), with its superior mechanical, chemical, and thermal properties, as well as high biocompatibility, has been used in aerospace, electronics, and biomedical applications. In this paper, a large number of experiments of single-pulse laser drilling on PEEK were performed to analyze the hole morphology and keyhole evolution, which were characterized by an optical microscope, charge-coupled device (CCD), and high-speed camera. A novel method is proposed to observe and measure the dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Because of its exceptional mechanical, chemical, and thermal qualities, it is employed in a wide range of applications, particularly in the aerospace, automotive, and electronics industries. PEEK is also frequently utilized in the medical sector for dental materials and bone restoration, due to its high biocompatibility and high thermal resistance [32]. Thermoplastic polyethylene (PE), which has a flexible crystal structure, is a lightweight, strong material.…”
Section: Materials Alternativesmentioning
confidence: 99%
“…Because of its exceptional mechanical, chemical, and thermal qualities, it is employed in a wide range of applications, particularly in the aerospace, automotive, and electronics industries. PEEK is also frequently utilized in the medical sector for dental materials and bone restoration, due to its high biocompatibility and high thermal resistance [32]. Thermoplastic polyethylene (PE), which has a flexible crystal structure, is a lightweight, strong material.…”
Section: Materials Alternativesmentioning
confidence: 99%
“…It was found that the PEEK implant abutments seem to be feasible, compared to zirconia implant abutments. Zhang et al [14] used the single-pulsed laser to drill PEEK. Results showed that the ejection is the primary material-removal mechanism during the slow increment stage, showing the dynamic process of keyhole evolution in the drilling of PEEK using the single-pulsed laser.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir processing on CuZn37/AA5056 is performed to study structural and phase evolution, with particular attention paid to intermetallic compound formation [ 11 ]. Finally, the laser/PEEK interaction is faced both experimentally and numerically to study the effect of pulse width and peak power on the geometrical morphology of the resulting hole [ 12 ].…”
mentioning
confidence: 99%